Reasoning 2008
DOI: 10.1017/cbo9780511814273.055
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Dog and Its Rational Tail: A Social Intuitionist Approach to Moral Judgment

Abstract: Research on moral judgment has been dominated by rationalist models, in which moral judgment is thought to be caused by moral reasoning. The author gives 4 reasons for considering the hypothesis that moral reasoning does not cause moral judgment; rather, moral reasoning is usually a post hoc construction, generated after a judgment has been reached. The social intuitionist model is presented as an alternative to rationalist models. The model is a social model in that it deemphasizes the private reasoning done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

119
3,208
9
240

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,913 publications
(3,576 citation statements)
references
References 120 publications
119
3,208
9
240
Order By: Relevance
“…They damn not only the nonpreferred outcome but also the procedure that led to it and the authorities who made the decision. Several different lines of research are consistent with the idea that affect may influence people's justice reasoning (e.g., Haidt, 2001). For example, Wheatley and Haidt (2005) found that hypnotically inducing people to feel disgust in response to neutral words led them to judge descriptions of acts that used those words as more morally wrong than did participants who had not been hypnotized to associate disgust with these words.…”
Section: The Anger Hypothesismentioning
confidence: 67%
See 2 more Smart Citations
“…They damn not only the nonpreferred outcome but also the procedure that led to it and the authorities who made the decision. Several different lines of research are consistent with the idea that affect may influence people's justice reasoning (e.g., Haidt, 2001). For example, Wheatley and Haidt (2005) found that hypnotically inducing people to feel disgust in response to neutral words led them to judge descriptions of acts that used those words as more morally wrong than did participants who had not been hypnotized to associate disgust with these words.…”
Section: The Anger Hypothesismentioning
confidence: 67%
“…For example, Haidt's (2001) social intuitionist model argues that people often make moral judgments quickly and intuitively on the basis of their gut-level reactions and that moral reasoning only comes into play when people are asked to justify their conclusions. Similarly, neuropsychological research suggests that people generate affect in conjunction with moral judgment and that these affective states subsequently guide moral judgment and choice (Damasio, 1994;Greene & Haidt, 2002;Greene, Sommerville, Nystrom, Darley, & Cohen, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been proposed that moral judgments are based on intuitive, tacit processes, while explicit justifications only count as post hoc rationalizations (Cushman, Young, & Hauser, 2006;Haidt, 2001Haidt, , 2003. However, as the present findings showed, while it is possible that affective responses (i.e., feeling of aversiveness) might operate tacitly and enable to distinguish affect-backed violations from conventional violations in both groups, emotion information is available for conscious processes of moral reasoning and is consistently cited during justification by people with typical development.…”
Section: Discussionmentioning
confidence: 99%
“…The first perspective claims that moral judgment is the product of conscious, effortful and sophisticated reasoning on the basis of explicit abstract principles (Piaget, 1965(Piaget, /1932Kohlberg, 1981); the second one relies on the assumption that morality takes the form of intuitions, accomplished by rapid, automatic, and unconscious affective responses (Haidt, 2001). In contrast with the 'conscious reasoning' perspective (Kohlberg, 1981), Haidt (2001) showed that when people are confronted with moral scenarios they engage in a process called 'moral dumbfounding' in which they are unable to articulate sufficient justifications for their confidently expressed moral judgments (Haidt, 0010-0277/$ -see front matter Ó 2011 Elsevier B.V. All rights reserved. doi:10.1016/j.cognition.2011.06.004 2001,2003) and that conscious reasoning only provides post hoc explanations for moral justifications.…”
Section: Introductionmentioning
confidence: 99%